Antimicrobial activity of chlorhexidine on Candida albicans and Streptococcus mutans isolated in children with early childhood caries – An in vitro study - Nipun Jain, Balagopal R Varma, Suresh J Kumar, Parvathy Kumaran, Arun Mamachan Xavier (Journal of Applied Pharmaceutical Science, 2023)
Streptococcus mutans and Candida albicans have a unique microbial feature that plays an essential role in early childhood caries (ECC). This study aimed to isolate C. albicans and S. mutans in children with ECC and observe the antimicrobial effect of 0.2% chlorhexidine (CHX). Children in the age group of 3–6 years were selected. The sample was collected using a sterile cotton swab from the tooth surface, streaked on sabouraud dextrose agar (HIMedia) plates, and incubated at 37°C for 24 hours. Disk diffusion and agar well diffusion methods were used to detect the susceptibility of C. albicans and S. mutans to 0.2% CHX. The mean zone of inhibition of CHX for C. albicans was 12.4 ± 0.59 mm, and S. mutans showed a zone of inhibition of 20.85 ± 1.18 mm. CHX was effective against both C. albicans and S. mutans, showing more antibacterial activity than antifungal activity.
Keywords: Chlorhexidine gluconate, Candida albicans, Streptococcus mutans, early childhood caries, anti